Secondary mortgage market (SMM): Is it right for financing housing in Ghana? (Journal of Science and Technology, 2016)
The formal housing finance system in Ghana is inadequate and highly underdeveloped. The formal finance institutions have provided very little mortgages particularly to the low and middle-income households. However, the fast growing capital market of Ghana offers an opportunity for sustainable housing finance in the country. This paper explores the possibility of addressing the housing finance problems in the country through the use of Secondary Mortgage Market (SMM). It does so by surveying the literature on SMM. It also examines the housing finance system in Ghana. It finds out that an SMM in principle will enable Ghana to overcome some of the constraints on the mortgage market and attract housing funds. But in practice it is not the best way of solving the housing finance problems in the country since the fundamentals are not right for a successful implementation of SMM. It notes that the scale of mortgage origination in the primary market is limited; the adjudication process is slow; collateralization is inadequate; and the land title regime is poor. It suggests that it is appropriate for Ghana to concentrate on solving these basic problems before any attempt at implementing a secondary mortgage market in the country.